1999
DOI: 10.1006/dbio.1999.9282
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Family Signal Transduction in Drosophila Development: From Mad to Smads

Abstract: The transforming growth factor-beta (TGF-beta) superfamily encompasses a large group of soluble extracellular proteins that are potent regulators of development in both vertebrates and invertebrates. Drosophila TGF-beta family members include three proteins with homology to vertebrate bone morphogenetic proteins (BMPs): Decapentaplegic (Dpp), Screw, and Glass bottom boat-60A. Genetic studies of Dpp signaling led to the identification of Smad proteins as central mediators of signal transduction by TGF-beta fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
227
0
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(234 citation statements)
references
References 159 publications
2
227
0
5
Order By: Relevance
“…Although we cannot rule out the possibility that the loss of Mad in these cells is compensated for by the presence of other wildtype CpCs in the niche, or that it may take longer than 12-14 days for the removal of Mad to have an effect, taken together our results suggest that the activation of the BMP pathway in the CpCs is not essential for GSC maintenance. These findings exclude a requirement for both gbb and dpp within the CpCs, as all BMP family ligands are believed to be mediated via Mad in Drosophila (Raftery and Sutherland, 1999). Thus, the ability of individual CpCs to perceive BMP ligands is not essential for the maintenance of GSCs with which they are in contact.…”
Section: Genetic Dissection Of Signaling Mechanisms Responsible For Gmentioning
confidence: 77%
See 2 more Smart Citations
“…Although we cannot rule out the possibility that the loss of Mad in these cells is compensated for by the presence of other wildtype CpCs in the niche, or that it may take longer than 12-14 days for the removal of Mad to have an effect, taken together our results suggest that the activation of the BMP pathway in the CpCs is not essential for GSC maintenance. These findings exclude a requirement for both gbb and dpp within the CpCs, as all BMP family ligands are believed to be mediated via Mad in Drosophila (Raftery and Sutherland, 1999). Thus, the ability of individual CpCs to perceive BMP ligands is not essential for the maintenance of GSCs with which they are in contact.…”
Section: Genetic Dissection Of Signaling Mechanisms Responsible For Gmentioning
confidence: 77%
“…However, other reports found dad-LacZ expressed in some IGS cells but not in the CpCs themselves (Song et al, 2004;Kirilly et al, 2005). To examine if the BMP pathway is functionally required in CpCs for GSC maintenance, we used bab1-Gal4 to drive the formation of mutant clones for the essential Smad effector, Mad (Raftery and Sutherland, 1999). We carefully examined mosaic germaria containing GSCs in contact only with Mad mutant CpCs and found that the lack of Mad expression in these cells 12-14 days after adult eclosion did not have any detectable effect upon GSC renewal ( Fig.…”
Section: Genetic Dissection Of Signaling Mechanisms Responsible For Gmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to Dpp signaling, an activated form of the Smad transcription factor, Mothers against dpp (Mad), is generated. Mad then binds to a related protein, Medea (Med), and this complex translocates to the nucleus to transcriptionally regulate expression of Dpp target genes (Raftery and Sutherland, 1999;Zimmerman and Padgett, 2000). In a number of cases, it has been observed that the Mad/Med complex binds the enhancers of Dpp target genes and directly activates transcription (Kim et al, 1997;Rushlow et al, 2001;Szuts et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Different kinds of TGFβs are involved in signal transduction between the extracellular environment and the nucleus. TGF-β 1, 2 and 3 are potent regulators in cellular development (Raftery andSutherland, 2002, Sefat, 2014b). Shah et al (1999) investigated the effect of manipulation of TGF-β on the wound healing process and found that the effects of TGF-β3 is inhibited by the high levels of TGF-β1and 2 from the inflammatory cells in adult tissue.…”
Section: Introductionmentioning
confidence: 99%